2013
DOI: 10.1111/hsc.12032
|View full text |Cite
|
Sign up to set email alerts
|

Carer and service providers’ experiences of individual funding models for children with a disability in rural and remote areas

Abstract: What is known about the topic• IF is increasingly favoured by governments globally.• IF has the potential to empower service users with more choice and access to new opportunities.• People with a disability living in rural and remote areas have fewer service choices on which to spend their IF. What this paper adds• Highlights the issues related to accessing IF in a rural and remote area.• Identifies benefits and barriers for rural and remote service users and service providers using IF models.• Suggests strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 18 publications
(38 reference statements)
2
94
0
Order By: Relevance
“…Of the 18 articles, 15 were original research papers from Australia (Dew et al . ), Finland (Eriksson ), New Zealand (Espiner & Hartnett ), Germany (Junne & Huber ), the United Kingdom (Mitchell ,b,c, ,b, Kendall & Cameron ) and the United States of America (Heller et al . , Gross et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 18 articles, 15 were original research papers from Australia (Dew et al . ), Finland (Eriksson ), New Zealand (Espiner & Hartnett ), Germany (Junne & Huber ), the United Kingdom (Mitchell ,b,c, ,b, Kendall & Cameron ) and the United States of America (Heller et al . , Gross et al .…”
Section: Resultsmentioning
confidence: 99%
“…); one included the perspectives of a combination of family members or caregivers and service providers (Dew et al . ); and two articles explored the perspectives of service users who had support from parents or guardians when necessary (Mitchell , Lombe et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this inadequate training over a third of participants in the study did not know what to ask professionals, and were reliant on the information they could find from other families. A more recent research study focusing on provider and carer experiences of individual funding (IF) models of disability, interviewed 10 parents of children with disabilities in rural NSW and found that both providers and carers reported a number of barriers in the uptake of IF packages including: lack of information and advice, limited local service options and capacity, higher costs and fewer services [28].…”
Section: Introductionmentioning
confidence: 99%
“…Improved choice is often argued to be an important result of individualized funding systems, and the evidence suggests that this is likely to be particularly challenging for those in rural and remote areas, where availability of services is restricted ( Dew et al 2013 ). In their study of individual budget pilots in England, Netten et al (2012Netten et al ( , 1568 found that those in receipt of these mechanisms reported a 'greater sense of control', and this was not dependent on the plan being in place or the level of resources allocated to the individual.…”
Section: Do Individual Budgets Improve Consumer Satisfaction and Outcmentioning
confidence: 99%
“…• Choice over whether to receive traditional services or self-manage; • Support appropriate to cognitive, physical and cultural needs to be an active participant in planning; • Mechanisms to review appropriate to capacity and individual needs; In their study of barriers to the use of individual budgets in rural and remote areas, Dew et al (2013) note similar challenges, including: a lack of information and advice; limited local service options and capacity; higher costs and fewer services; and the complexity of self-managing individual funding packages.…”
Section: Do Individual Budgets Improve Consumer Satisfaction and Outcmentioning
confidence: 99%